Bilingual education : from compensatory to quality schooling - Brisk, María Estela, 1940- (L. Erlbaum Associates, Publishers, 2006)
Bilingual Education: From Compensatory to Quality Schooling, Second Edition maintains its original purpose of synthesizing the research on successful bilingual education in order to demonstrate that quality bilingual education is possible and desirable. Findings from a wide range of studies are integrated to provide a clear picture of bilingual education in today's schools, and a professional understanding of the foundations and issues surrounding bilingual education programs. The recommendations offered provide a comprehensive basis for planning, developing, improving, and evaluating bilingual.